A review on farm household modelling with a focus on climate change adaptation and mitigation - Wijk, Mark T. van; Rufino, Mariana C.; Enahoro, Dolapo K.; Parsons, D.; Silvestri, Silvia; Valdivia, Roberto O.; Herrero, Mario (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
This study systematically reviewed the literature to evaluate how suitable existing farm and farm household models are to study aspects of food security in relation to climate change adaptation, risk management and mitigation. We systematically scanned approximately 16,000 research articles covering more than a 1000 models. We found 126 models that met the criteria for subsequent detailed analysis. Although many models use climate as an input, few were used to study climate change adaptation or mitigation at farm level. Promising mixtures of methodologies include mathematical programming for farm level decision-making, dynamic simulation for the production components and agent based modelling for the spread of information and technologies between farmers. There is a need for more explicit farm level analyses with a focus on adaptation, vulnerability and risk. In general terms, this systematic review concludes that there are enough techniques for integrated assessments of farm systems in relation to climate change, adaptation and mitigation, but they have not yet been combined in a way that is meaningful to farm level decision makers.